The Hadith of Rajab Fasting in A Simultaneous Reserch - Damanhuri Damanhuri (Ar-Raniry: International Journal of Islamic Studies, 2016)
The researched Hadith of Prophet Muhammad SAW about Rajab fasting was a narrated hadith of Ibn ‘Abbas booked by Muslim. In hadith above, there were some narrators/rawi such as Abu Bakr Ibn Aby Shaybah, Abd Allah Ibn Numair, Uthman Ibn Hakim al Ansari, Sa’id Ibn Jubayr and Abd Allah Ibn ‘Abbas. In his partial analyses, there were some conclusions that: 1. All of narrators that involved in Hadith sanad were qualified: 2. Thiqa, All the narrators met with another narrators as the teachers: 3. And the hadith matan was free from shadh aspect: 4. The hadith matan was free from illat. So it can be concluded that narrated hadiths of Anas Ibn Malik which were collected by Muslim were qualified (sahih). In simultaneous analyzes, found that that hadith had 4 (four) tabi’ qasir. Because all of the narrators who were narrated by Muslim were thiqah qualified and the sanad connectivity was also muttasil, so the present of 4 tabi’ ´hadiths couldn’t improve the quality of main hadith sanad or mutaba’ that had been sahih in quality. Later on, simultaneously, that hadith had 4 (four) shahid ma’nawi hadiths. Those hadiths were narrated by 4 (four) different friends, as: Sa’id Ibn Sa’id, Anas Ibn Malik, ‘Abd Allah Ibn ‘Umar, and Abi Dharr. So the hadith of Rajab fasting had been narrated by 5 (five) friends. Thus, quantitatively, those hadiths improved to be mashhur (ahad mashhur) because they were narrated by five friends.